2014
DOI: 10.1016/j.bjane.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endovascular removal of intracardiac migrated port A catheter in a child with acute lymphoblastic leukemia

Abstract: A 2-year-old boy with acute lymphoblastic leukemia was presented with peripherally inserted central catheter dysfunction. Radiological examinations revealed a catheter remnant in the right atrium extending into pulmonary vein. The catheter remnant was successfully removed from the right atrium by percutaneous endovascular intervention without any complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“… 1 , 4 This type of catheter reduces the risk of leakage of irritant chemotherapy substances, offers continuous access, and avoids the discomfort of multiple vein punctures. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 4 This type of catheter reduces the risk of leakage of irritant chemotherapy substances, offers continuous access, and avoids the discomfort of multiple vein punctures. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that, despite the rarity of their occurrence, using a TIVAP involves the potential for complications, such as infection, embolization, catheter occlusion, venous perforation, atrial perforation, arrhythmia, phlebitis, leakage, migration, and catheter fracture, among others. 5 - 8 These complications can be classified as early complications (within 7 days of implantation) or late complications (after this period). 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that application of port catheters is safe. Complications after catheter insertion include embolization, infection, venous thrombosis, occlusion of the catheters, venous perforation, atrial perforation, arrhythmias, flebitis, leakage, dislodgement, subintimal entrapment, and fracture and/or migration of the catheters (11)(12)(13)(14)(15). Port-a-Catheter fracture with or without embolization is a serious and rare complication in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…While surgery was the only choice in the treatment of broken and migrated catheters in the past, currently, percutaneous transcatheter retrieval of the portacath fractured fragment by interventional endovascular techniques is the most common technique and successfully performed with much lower morbidity and mortality rates when compared with surgery in adult patients even in neonates (1,5,6,14,(23)(24)(25). The reported success rates of percutaneous retrieval of fractured fragment in the literature are between 71% and 100% (5,17,25).…”
Section: Discussionmentioning
confidence: 99%